2005
DOI: 10.1002/ijc.20961
|View full text |Cite
|
Sign up to set email alerts
|

Retinoid‐related molecule AGN193198 potently induces G2M arrest and apoptosis in bladder cancer cells

Abstract: The novel synthetic retinoid-related molecule 4-[3-(1-heptyl-4,4-dimethyl-2-oxo-1,2,3,4-tetrahydroquinolin-6-yl)-3-oxo-propenyl]-benzoic acid (AGN193198) neither binds effectively to retinoic acid receptors (RARs) and retinoid X receptors (RXRs) nor transactivates in RAR-and RXR-mediated reporter assays. Even so, AGN193198 is potent in inducing apoptosis in human prostate and breast carcinoma cells (Keedwell et al., Cancer Res 2004;64:3302-12). Here, we extend these findings to show that AGN193198 potently and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…Furthermore, this induced DNA damage could be the basis for the arrest of cells in the S-phase of the cell cycle detected in cells after MTA treatment. In accordance with our results, previous studies have shown that cell cycle arrest may occur as a result of DNA damage, in order to allow DNA repair and prevent entry into mitosis in the presence of damaged DNA [27,28]. …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, this induced DNA damage could be the basis for the arrest of cells in the S-phase of the cell cycle detected in cells after MTA treatment. In accordance with our results, previous studies have shown that cell cycle arrest may occur as a result of DNA damage, in order to allow DNA repair and prevent entry into mitosis in the presence of damaged DNA [27,28]. …”
Section: Discussionsupporting
confidence: 92%
“…The mechanism by means of which an oxidative stimulus can activate the caspase cascade during apoptosis has not been fully characterized; nevertheless, oxygen and its compounds is known to be able to deplete reduced glutathione or damage the cellular antioxidant defence system [35]. This leads to increased intracellular levels of ROS which are responsible for inducing DNA damage and p53 activation with subsequent apoptosis [4,28,36]. Furthermore, some proapoptotic agents, such as certain histone deacetylase inhibitors, induce caspase-independent apoptosis through the generation of ROS [37].…”
Section: Discussionmentioning
confidence: 99%
“…This is further corroborated in decrease from C3 to TCC) was reported to be a marker for bladder cancer when human urine was analysed via headspace GC-MS. 46 Other chemicals have been reported in the medical literature, but not as cancer markers. For example, piperitone has been reported to inhibit the cervical cancer cell-line growths, 47 benzoic acid (suggested in Table 4 to increase from C3 to TCC) reduces bladder cancer when as a functional group within the retinoid-related molecule AGN193198, 48 and butyrophenone (suggested in Table 4 to increase from C3 to TCC) is employed in the treatment of schizophrenia and other central nervous disorders 49 though it is unclear if any patients were taking this medication. It should be noted that some biomarkers are almost ubiquitous biomarkers and can be seen as volatile compounds emanating from biological systems; examples include: dimethyl disulphide, 2-butanone, 2-propanol, acetic acid, etc.…”
Section: Diagnostic Potentialmentioning
confidence: 99%
“…1 ). Similar to MX781, AGN193198 induced G2/M arrest followed by apoptosis in pancreatic and bladder cancer cells [139,140]. In contrast to MX781, AGN193198 has been shown not to inhibit IKK in prostate cancer cells [138], although its effect on recombinant kinases has not been reported yet.…”
Section: Novel Analogs Of Cd437mentioning
confidence: 97%